Epicuticular Waxes from Solanum nigrum Complex: Chemotaxonomic Implications - Mohy-ud-din, A.; Khan, Z.; Ahmad, M.; Kashmiri, M.A.; Yasmin, S.; Asghar, M.N.; Ahmad, S.R. (Asian Journal of Chemistry, 2010)
Chemotaxonomic studies of five locally available plant taxa of Solanum nigrum complex were carried out in order to resolve the international taxonomic controversy about these plants. GCMS analysis of the n-hexane-extracted epicuticular waxes of S. americanum, S. chenopodioides, S. retroflexum, S. nigrum and S. villosum showed the presence of squalene, phytol, palmitic acid, linolenic acid, ester of palmitoleic acid along with a variety of hydrocarbons as the chemical constituents of these waxes. The presence of the hydrocarbons, alcohols, some of the esters, acids, aldehyde and ketone in the epicuticular wax of S. nigrum had never been reported in the literature. Multivariate analysis was employed for grouping of these five taxa on the basis of constituents of the epicuticular waxes. The significant distance found between S. chenopodioides and S. villosum as well as in americanum and S. nigrum, in their respective clusters, indicated them as distinct species. But S. retroflexum did not show such a marked difference and hence might be regarded as a variety or subspecies of S. nigrum.